[Fresh Lava Rock Road Near Askja] - Streng, Evelyn Fiedler (1975)
Photograph of a fresh lava rock road near Askja. The red, bumpy road curves through the dark, rocky plain covering the foreground. A white car is visible in the background at the center of the photograph. A snowy mountain range crosses the background.